Grossman's Cardiac Catheterization, Angiography, and Intervention. - Baim, Donald S. (Wolters Kluwer Health, 2005)
The premier reference on cardiac catheterization is now in its thoroughly revised Seventh Edition, reflecting the rapid evolution and growing clinical use of interventional techniques. The completely revamped interventional section includes new material on treatment of pediatric and adult congenital heart disease, as well as on coronary atherectomy, thrombectomy, distal embolic protection devices, bare metal and drug-eluting stents, and percutaneous valve therapies. Other significantly revised chapters include pulmonary angiography, endomyocardial biopsy, and circulatory assist devices. This e.